Synthesis and Biological Evaluation of a Fused Structure of Indolizine and Pyrrolo[1,2-c]pyrimidine: Identification of Its Potent Anticancer Activity against Liver Cancer Cells - Seonghyeon Nam; Yechan Lee; So-Hyeon Park; Wan Namkung; Ikyon Kim (MDPI AG, 2022)
A highly efficient approach to a new indolizine scaffold fused with pyrrolo[1,2-c]pyrimidine was achieved via one-pot three-component coupling followed by an oxidative cyclization reaction. The simple two-step sequence allowed rapid access to various tetracyclic compounds from commercially available starting materials with the formation of five new bonds. Here, we observed the effects of these compounds on cell viability in HepG2, H1299, HT29, AGS, and A549 cancer cell lines. Interestingly, this fused scaffold had more potent anticancer activity in hepatocellular carcinoma HepG2 and Huh7 cells than other cancer cells. In particular, 5r strongly decreased cell viability in HepG2 and Huh7 cells with an IC50 value of 0.22 ± 0.08 and 0.10 ± 0.11 µM, respectively, but had a very weak inhibitory effect on the cell viability of other cancer cell lines. In addition, 5r significantly inhibited cell migration and induced apoptosis in HepG2 and Huh7 cells via the activation of caspase-3 and cleavage of PARP in a dose-dependent manner. Notably, the co-treatment of 5r with gemcitabine resulted in the significant additional inhibition of cell viability in HepG2 and Huh7 cells. Our results suggest that 5r could be used to develop new chemotype anticancer agents against liver cancers.